Vibration induced by subway trains: open-trench mitigation analysis in the time and frequency domains - Yang, Wenbo; Yuan, Ran; Wang, Juan (Hindawi, 2018)
In this paper, we analyse the mitigation effects of open trenches on the vibrations induced by subway trains. The study is performed by using both physical model tests and numerical simulations. The effectiveness is evaluated by calculating the frequency response function (FRF) and the vibration acceleration peak (VAP) in both time and frequency domains. The experimental and numerical results demonstrate that the open trench has clear effects on the dynamic soil response. Both time and frequency domain results suggest that the dynamic response of the soils beyond the open trenches could be significantly affected, due to the existence of the open trench. According to the frequency domain analysis, the inclusion of open trenches could effectively reduce the soil response in a higher frequency range. Due to reflection effects at the boundaries of the trench, an amplification of the soil response in front of the open trench is observed. Parametric study by means of numerical simulations is also performed. The width of the open trench demonstrates negligible effects on the dynamic soil response, whilst the trench depth exhibits a large influence on the trench isolation performance. With an increase in the trench depth, the isolation performance is significantly improved. It is concluded that the open trenches perform well as an isolation barrier, in mitigating the vibration induced by subway trains.